Recycling of epdm waste : effect of recycled epdm (R-EPDM) loading to mechanical and characterization properties of PP/R-epdm blends / Nur Aziera Abdul Manaf - Abdul Manaf, Nur Aziera (2020)
In this work, thermoplastic elastomers (TPE) were produced based on polypropylene (PP) and recycled ethylene propylene diene monomer (R-EPDM) through the internal mixer. The effect of addition amount of filler loading of recycled ethylene propylene diene monomer (R-EPDM) filled polypropylene composite was studied on the tensile test, impact test and characterization of final composite. For sample preparation, five sample with different R-EPDM loading 0%, 10%, 20%, 30% and 40% were prepared. For the mechanical properties result, the highest tensile strength and Young’s Modulus show at 0% of R-EPDM loading and the highest elongation at break show at 20% of R-EPDM filler loading. The addition of R-EPDM loading decreased the tensile strength and the Young’s Modulus, but the elongation at break showed significant improvement.